Critical Quality Attributes of Lipid Nanoparticles for mRNA: Selection, Justification, and Control - U. A. Efremova; I. I. Terninko (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION. Lipid nanoparticles represent a promising platform for targeted drug delivery, including nucleic acids, as demonstrated by COVID-19 vaccines. Unlike conventional dosage forms, lipid nanoparticles are complex supramolecular systems where the formation of critical quality attributes occurs during nanoparticle self-assembly and is not subject to post-production correction. The traditional approach based on end‑product testing is insufficient, which justifies the implementation of the Quality by Design philosophy integrating the requirements of ICH Q8, Q9 and Q10. AIM. Systematic analysis of existing methodological approaches for the determination, assessment, and quality control of lipid nanoparticles for mRNA, and identification of critical quality attributes in accordance with the requirements of ICH guidelines Q8(R2), Q9, and Q10. MATERIALS AND METHODS. A systematic analysis of ICH Q8–Q10 guidelines was performed. For quantitative risk assessment, the Failure Mode, Effects, and Criticality Analysis method was applied with the calculation of the Risk Priority Number (critical threshold ≥ 50). The Ishikawa diagram was used to systematically identify factors affecting the critical quality attributes of lipid nanoparticles for mRNA. RESULTS. The highest Risk Priority Number values were obtained for encapsulation efficiency (100), particle size (80), mRNA content (75), polydispersity index (64), and lipid composition (60). pH and osmolality were non‑critical (8). Five categories of risk factors were identified: manufacturing process, equipment, raw materials, working conditions, and personnel. Based on the identified critical quality attributes for mRNA, a three‑level manufacturing control strategy was developed for lipid nanoparticles for mRNA: incoming raw material control, in‑process control using Process Analytical Technology, and final release testing with validated methods according to ICH Q2(R2). CONCLUSIONS. The implementation of Quality by Design in the development and manufacturing of lipid nanoparticles for mRNA is scientifically justified. The proposed approach, including Failure Mode, Effects, and Criticality Analysis and the Ishikawa diagram, can be adapted for specific processes and products. Based on the identified critical quality parameters, a three-level quality strategy was developed covering every stage of lipid nanoparticle manufacturing for mRNA.